Efektivitas Penerapan Model Pembelajaran Quick On The Draw Terhadap Kemandirian Belajar Pendidikan Agama Islam - kiki nazira; Umi Hijriyah; Agus Susanti (Jurnal Bilqolam Pendidikan Islam, 2025)
This study aims to examine the effectiveness of implementing the Quick on the Draw learning model on students’ learning independence in Islamic Religious Education (IRE), with a particular focus on the initiative or creativity aspect. The research employed a quantitative approach using a quasi-experimental design with a posttest-only control group. The research sample consisted of Grade VIII G as the experimental group and Grade VIII C as the control group at SMP Negeri 36 Bandar Lampung. Data were collected through a learning independence questionnaire that had been validated and tested for reliability, and subsequently analyzed using an Independent Samples t-test. The results indicate that, empirically, there is a significant difference in learning independence between the experimental and control groups, with a significance value of 0.000 (p < 0.05). These findings suggest that the Quick on the Draw model is effective in enhancing students’ learning independence. The novelty of this study lies in its focus on the affective domain of learning independence within the context of Islamic Religious Education at the public junior secondary school level. The implications of this study contribute to the development of active and student-centered learning approaches oriented toward character formation.